MODEL PENINGKATAN KINERJA MANAJERIAL MELALUI PARTISIPASI PENYUSUNAN ANGGARAN DAN JOB RELEVANT INFORMATION (JRI) (Studi Kasus Pada Universitas Diponegoro Semarang) - Sutapa Sutapa; Choiriyah Choiriyah (Universitas Islam Sultan Agung (UNISSULA), Faculty of Economics, Department of Accounting, 2013)
The present study aims to examine the relationship between budget participation on managerial performance in public sector organizations (Study at Diponegoro University). It also attempts to examines whether the Job Relevant Information (JRI) as an intervening variable between budgetary participation and managerial performance. The data used in this study is based on individual perception of the Head of the sub-division and the head of the division who filled out the questionnaire and returned to the researcher. There are 55 questionnaires distributed to therespondents, the number of questionnaires returned by 48 questionnaires (87%). Data analysis is done by using the SEM (Structural Equation Model) with PLS software. These results indicate that budgetary participation and significant positive effect on managerial performance. Participation in the managing of budgets gave the positive and significant towards the job relevant information (JRI). Job Relevant Information (JRI) gave positive and significant towards managerial performance. However, in testing of the relationship between budgetary participation and managerial performance through job relevant information (JRI) as an intervening variable, showed a positive but not significant.